Pelatihan tes Uji Kemahiran Berbahasa Indonesia (UKBI) di SMK Al–Husna Bojong Gede - Vickry Ramdhan; Randi Ramliyana; Usman Sutisna (Universitas Hamzanwadi, 2022)
Language skills are needed at all times in every segment of social life. The level of sound and correct Indonesian language skills differs for each individual. Testing a person's ability to speak Indonesian both verbally and in writing can be done by undergoing the